2015
DOI: 10.1186/s13148-015-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and transgenerational epigenetic inheritance: evidence in asthma and COPD?

Abstract: Evidence is now emerging that early life environment can have lifelong effects on metabolic, cardiovascular, and pulmonary function in offspring, a concept also known as fetal or developmental programming. In mammals, developmental programming is thought to occur mainly via epigenetic mechanisms, which include DNA methylation, histone modifications, and expression of non-coding RNAs. The effects of developmental programming can be induced by the intrauterine environment, leading to intergenerational epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 174 publications
2
37
0
Order By: Relevance
“…Emerging findings have been pointed out that epigenetic mechanisms exert a pivotal role in COPD physiopathology (Krauss-Etschmann et al, 2015). Epigenetic has been defined as dynamic regulation of gene expression in response to external stimuli independent that is independent of changes in the underlying DNA sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging findings have been pointed out that epigenetic mechanisms exert a pivotal role in COPD physiopathology (Krauss-Etschmann et al, 2015). Epigenetic has been defined as dynamic regulation of gene expression in response to external stimuli independent that is independent of changes in the underlying DNA sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already demonstrated global hypomethylation and hypermethylation of tumor suppressor genes in lung cancer patients, which could be rescued by effective treatments1415. Other studies have also revealed abnormal DNA methylation status in patients with asthma161718 and COPD1920. In addition, abnormal histone acetylation (for instance, H3K9ac, H3K18ac, and H4K16ac), which could be rescued by effective treatments, is also associated with respiratory diseases212223.…”
mentioning
confidence: 98%
“…However, we observed a stronger impact of parental BHR and IgEs measured before conception, suggesting that parental preconception disease activity in itself might affect respiratory health in offspring. Based on newly observed epigenetic inheritance in animal models and our findings, we hypothesize that ongoing respiratory and allergic disease activity in humans might cause epigenetic changes that can be inherited to the next generation, manifesting phenotypic characteristics in the offspring. Although this is biologically plausible given experimental research results , this has not been described in humans to date.…”
Section: Discussionmentioning
confidence: 62%